Metabolomic Response to Drought Stress in Belosynapsis ciliata (Blume) ‘Qiuhong’ - Yongquan Li; Bipei Zhang; Runsheng Huang; Min Wen; Leying Huang; Yiting Su; Yanjun Sun; Ning Wang; Wei Guo (Agronomy, 2022)
The drought stress responses of plants are complex regulatory mechanisms that include various physiological responses reflected by the global metabolic status. Metabolomics is an effective, analytical, and instrumental technique for informatics/statistics for the acquisition of comprehensive information on metabolites. We investigate the effect of drought stress on a Belosynapsis ciliata cultivar, ‘Qiuhong’ (a drought-tolerant cultivar), using liquid chromatography-mass spectrometry based on a widely targeted metabolomic approach. ‘Qiuhong’ leaves are subjected to 15- and 30-day drought treatments and are then compared to a control group without drought stress and a rehydration group. In total, 290 differentially accumulated metabolites were detected between drought and normal conditions through multivariate statistical analyses, of which 65 metabolites (36 upregulated and 29 downregulated) were highlighted for their significant contribution to drought tolerance, including an anthocyanin (peonidin 3-O-galactoside) that caused the purple-red hue in leaves under drought stress. In addition, we found that two significantly altered pathways (citrate cycle and purine metabolism) were related to enhanced drought tolerance in plants. Notably, the synthesis of three compounds (p-coumaroyl putrescine, apigenin 6-C-glucoside, and β-nicotinamide mononucleotide) was specifically induced in the drought-treated ‘Qiuhong’, indicating their critical roles in drought resistance. Our results provide a foundation for further research on drought-resistant mechanisms in B. ciliata.